(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Circuit Tourism is a multi-centre, multi- destination travel arrangement. Circuit tourism involves visits to more than one destination during a trip away from home. Bihar is one of the oldest inhabited places in the World with history of thousands of years. The rich culture and heritage of the Bihar is evident from the innumerable monuments, temples and shrines dotted all over the state. Bihar is also trying to promote tourism by developing cluster of tourist centres, also called as circuits. It is making efforts to make religious and pilgrimage tourism destinations more attractive, with suitable tour packages and facilities. However, the plan to promote pilgrimage circuits has been marred by diverse range of problems. The paper aims to identify the Buddhist pilgrimage tourism circuit of Bihar. It also intends to examine the level of backward and forward linkages in the development and functioning of Buddhist pilgrimage tourism circuit in the state. It aims to bring forth the major bottlenecks in the successful implementation of Buddhist circuit tourism model in Bihar. Finally, it explores the opportunities and potential to strengthen and streamline Buddhist pilgrimage tourism circuit at the state level. The study is largely interpretative in nature and mostly based on the interpretation and analysis of secondary data, using mixed research methodologies.